2014
DOI: 10.1093/carcin/bgu321
|View full text |Cite
|
Sign up to set email alerts
|

To be an ally or an adversary in bladder cancer: the NF-κB story has not unfolded

Abstract: Signaling and regulation of transcription factor nuclear factor-kappaB (NF-κB) has been an area of extensive research since its first discovery nearly three decades ago. Members of the NF-κB family have been reported to critically mediate a multitude of responses in normal cells. Therefore, it is not surprising that NF-κB function can go awry and result in pathological conditions including cancer. Despite its critical importance, the functional role of NF-κB has not received the same attention in cancers of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 74 publications
0
31
0
1
Order By: Relevance
“…NF‐κB p50/p65 heterodimer is critical mediator for tumorigenesis and cancer progression. A number of tumor progression‐associated proteins which modulate proliferation, anti‐apoptosis, angiogenesis, and metastasis are encoded by NF‐κB target genes and upregulated with active NF‐κB signaling in bladder cancer . Constitutive NF‐κB activation was observed in high grade bladder cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF‐κB p50/p65 heterodimer is critical mediator for tumorigenesis and cancer progression. A number of tumor progression‐associated proteins which modulate proliferation, anti‐apoptosis, angiogenesis, and metastasis are encoded by NF‐κB target genes and upregulated with active NF‐κB signaling in bladder cancer . Constitutive NF‐κB activation was observed in high grade bladder cancer .…”
Section: Discussionmentioning
confidence: 99%
“…A number of tumor progression-associated proteins which modulate proliferation, antiapoptosis, angiogenesis, and metastasis are encoded by NF-κB target genes and upregulated with active NF-κB signaling in bladder cancer. 29,30 Constitutive NF-κB activation was observed in high grade bladder cancer. 31 Many studies indicated inhibition of NF-κB activation suppresses tumor growth, anti-apoptosis, angiogenesis, and metastatic potential in bladder cancer in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Other functions of NF-kB, without the involvement of inflammation, are also thought to associate with the promotion of tumorigenesis. These include stimulation of cell proliferation, prevention of apoptosis, regulation of angiogenesis, and immortalization via regulating the expression/function of oncogenes, antiapoptotic genes, angiogenic factors, and telomerases, respectively (35). In urothelial cancer, associations between polymorphisms in the NF-kB1/ p50 gene, which could form a heterodimer with p65 as the NF-kB activator, and the risk of tumor development or recurrence have been reported (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, deletion of chromosome 9 is detected in the majority of cases of non-muscle invasive bladder cancer (7). In addition, factors associated with bladder cancer include the phosphatidylinositol-3-kinase/protein kinase B/mechanistic target of rapamycin pathway, RAS, cell cycle progression and receptor tyrosine kinases (8)(9)(10). Two bladder cancer cell lines, 253J B-V and 253J, were used in the present study.…”
Section: Introductionmentioning
confidence: 99%